Question Prompts in Teaching Relevant and Authentic Texts to Improve Students’ Reading Competence During Pandemic Covid-19 Outbreak - Suparman, Ujang (FKIP Universitas Lampung, 2021)
Question Prompts in Teaching Relevant and Authentic Texts to Improve Students’ Reading Competence During Pandemic Covid-19 Outbreak. Objectives: This research investigates whether: 1) QPs and relevant and authentic texts can improve students’ reading ability especially during the outbreak of pandemic Covid-19, and 2) there is any effect of students’ gender on their reading ability. Methods: Quantitative approach was used with one-group pretest-posttest design. The data were analyzed using descriptive statistics and t-test. Findings: the use of QPs can improve student reading ability especially during the outbreak of pandemic Covid-19, there is difference in students’ reading ability before and after using QPs in teaching authentic texts, but there is no difference in reading ability by gender. Conclusion: Findings provide implications to add the body of knowledge relevant to the theories about the acquisition of English as an ESL or EFL during the pandemic Covid 19.Keywords: reading comprehension ability, question prompts, relevant and authentic texts.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202101